Influence of geochemical processes on the geomechanical response of the overburden due to CO2 storage in saline aquifers. (November 2015) - Varre, Sai B.K.; Siriwardane, Hema J.; Gondle, Raj K.; Bromhal, Grant S.; Chandrasekar, Vikram; Sams, Neal
Graphical abstract: Highlights: Investigated geochemical influence on geomechanical response during CO2 storage. Coupled multiphase fluid flow and geomechanical modeling. Coupled single-phase fluid flow and geomechanical modeling. Geochemical influence is very small for the mineralogical composition considered. Compared single-phase and multiphase fluid flow models coupled with geomechanics. Abstract: The objective of the study is to investigate the influence of geochemical processes on the geomechanical response of overburden during and after CO2 injection. In the current study, coupled multiphase fluid flow and geomechanical modeling with geochemical processes were performed to simulate large-scale injection of CO2 (up to 10 million metric tonnes per year) into a deep saline aquifer over the long-term (up to 1000 years). The geochemical modeling results show that geochemical processes, such as mineral dissolution and precipitation, do not have a significant influence on reservoir rock porosity (about 2% reduction). Modeling results show that the inclusion of geochemical reactions in the coupled fluid flow and geomechanical models do not have any significant influence on the computed pressure and ground displacements due to CO2 injection for the typical mineralogical composition considered in this study. In other words, a coupled single-phase fluid flow and geomechanical model would give similar results at a significantly lower computational effort.